2023
DOI: 10.3389/fimmu.2023.1107670
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species and mitochondrial damage in rheumatoid arthritis and targeted drugs

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation, pannus formation, and bone and cartilage damage. It has a high disability rate. The hypoxic microenvironment of RA joints can cause reactive oxygen species (ROS) accumulation and mitochondrial damage, which not only affect the metabolic processes of immune cells and pathological changes in fibroblastic synovial cells but also upregulate the expression of several inflammatory pathways, ultimately promoting inflammation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 304 publications
0
29
0
Order By: Relevance
“…This endoplasmic reticulum stress may promote the progression of RA through the proliferation of synovial cells and the production of pro-inflammatory cytokines ( de Seabra Rodrigues Dias et al, 2021 ; Floudas et al, 2022 ; Miglioranza Scavuzzi and Holoshitz, 2022 ). Wulf et al pointed out that oxidative stress in mitochondria can produce many reactive oxygen species (ROS) ( Jing et al, 2023 ). At high concentrations, free radicals and their derivatives are harmful to the organism and destroy all the main components of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This endoplasmic reticulum stress may promote the progression of RA through the proliferation of synovial cells and the production of pro-inflammatory cytokines ( de Seabra Rodrigues Dias et al, 2021 ; Floudas et al, 2022 ; Miglioranza Scavuzzi and Holoshitz, 2022 ). Wulf et al pointed out that oxidative stress in mitochondria can produce many reactive oxygen species (ROS) ( Jing et al, 2023 ). At high concentrations, free radicals and their derivatives are harmful to the organism and destroy all the main components of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…This Floudas et al, 2022;Miglioranza Scavuzzi and Holoshitz, 2022). Wulf et al pointed out that oxidative stress in mitochondria can produce many reactive oxygen species (ROS) (Jing et al, 2023). At high concentrations, free radicals and their derivatives are harmful to the organism and destroy all the main components of the cell.…”
Section: Figurementioning
confidence: 99%
“…We all know that oxidative stress is associated with inflammation and both factors are closely linked to RA, oxidative stress affects immune cell metabolic processes and promotes inflammation in RA, 15 Therefore, some traditional medications operate through a new mechanism of inhibiting oxidative stress and increasing antioxidants to alleviate clinical symptoms in patients with RA 16 . The results of our study demonstrated elevated MDA expression and significantly decreased SOD and TAOC expression in the serum of RA patients, suggesting an imbalance of oxidative homeostasis and immune inflammatory response in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Fibroblast-like synoviocytes (FLS) are the primary effect cells sustaining joint inflammation, angiogenesis, and cartilage destruction. 7 During RA activity, FLS produces a multitude of angiogenic factors, including vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), which pathologically alter endothelial cell activity and promote joint angiogenesis. This exacerbates RA severity by contributing to synovial hyperplasia and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis is crucial for various physiological processes, including embryonic development, wound healing, and tissue regeneration, as well as pathophysiological conditions like cancer and inflammation 6 . Fibroblast‐like synoviocytes (FLS) are the primary effect cells sustaining joint inflammation, angiogenesis, and cartilage destruction 7 . During RA activity, FLS produces a multitude of angiogenic factors, including vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), which pathologically alter endothelial cell activity and promote joint angiogenesis.…”
Section: Introductionmentioning
confidence: 99%